Pengaruh Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), Dana Bagi Hasil (DBH) Terhadap Belanja Modal (Studi Empiris Pada Pemerintah Kota/Kabupaten di Jawa Tengah Tahun 2011-2014) - Putranto, Galih; , Drs. Wahyono, M.A, Akt, CA (2017)
This research aims to provide empirical evidence by using secondary data, regarding to the effect of the General location Fund (DAU), Special Allocation Fund (DAK), Revenue-Sharing Funds (DBH) to the Capital Expenditure. heresearcher used Local Government of Regency/ City in central of java as a sample in 2011-2014 as many a 35. The sampling technique for this study is saturated sample. The researcher used descriptive analysis method for this research. The esearcher used test hypothesis as the data analysis technique which include multiple linear, F test, test and test t R2. All of the data collected, processed using the test the classical assumption of normality test, ocorrelation,multicollinearity test, and test heterokedastisitas.Based on the results of statistical tests t-count probabalitas DAU 0,000 <α = 0.05, t-count DAK probability of 0.087> α = 0.05, DBH t-count probability of 0,003 <α = 0.05. This shows that the GAF and RSF affect the significance of the Capital Expenditure, while SAF no significant effect on Capital Expenditure.